The dermatology life quality index as a means to assess life quality in patients with different scar types - Reinholz, Markus; Poetschke, J.; Schwaiger, H.; Epple, Andreas; Ruzicka, T.; Gauglitz, G. G. (Journal of the European Academy of Dermatology and Venereology, 2015)
Background Measuring quality of life through questionnaires is a common method to evaluate the impact of different afflictions on the patient's well-being, especially in the field of dermatology where appearance changing afflictions are common. Objectives A variety of questionnaires has been used to distinguish different skin conditions like psoriasis, atopic dermatitis and scars. Using the Dermatology Life Quality Index (DLQI), we investigated different scar types regarding their impact on quality of life. Methods We assessed the quality of life in 130 patients presenting to our outpatient scar clinic for the first time using the DLQI. Scars were analysed according to their clinical appearance (physiological scars, keloids, hypertrophic scars, atrophic scars, self-harm scars). Physiological scars were established as a baseline for further comparison between groups. Results Patients in the physiological scar group scored a mean DLQI score of 2.07 ± 3.56, patients in the keloid-, hypertrophic scar-, atrophic scar- and self-harm scar group scored values of 6.06 ± 4.00, 2.53 ± 2.48, 7.26 ± 6.72 and 12.00 ± 3.85 respectively. When compared to the baseline group the difference in the overall score for keloids was +3.99 (P < 0.001), hypertrophic scars scored +0.45 (ns), atrophic scars +5.19 (P < 0.01) and self-harm scars +9.93 (P < 0.001). Conclusion Using the DLQI, we could demonstrate that different subsets of pathological scars do affect patients in a different magnitude. The DLQI provides a promising adjunct for quantifying the quality of life in patients suffering from keloids, atrophic- and self-harm scars and may constitute an interesting additional tool for monitoring the progress of scar treatments.